Effectiveness of a Local Food–Based Balanced Nutrition Guide (LFBNG) in Improving Knowledge of Community Health Cadres and Stakeholders for Stunting and Anemia Prevention - Priyo Sulistiyono; Yeni Fitrianingsih; Suratmi Suratmi; Rahmani Azzahra (Jurnal Medisci, 2026)
Background: Stunting and anemia among children aged 6-23 months remain a priority health problem in Indonesia, with a prevalence of 21.6% in 2022. A local food-based balanced nutrition guideline (PGS-PL), developed using Optifood Linear Programming, was introduced as an evidence-based, locally adapted nutrition education tool for the Talun Community Health Center working area, Cirebon Regency. Aim: This study aimed to evaluate the effectiveness of PGS-PL education in improving the knowledge of cadres and local stakeholders as a feasibility step prior to community-wide implementation. Methods: A one-group pre-test post-test design was applied to 17 participants (cadres, civil servants, police officers, village officials, and entrepreneurs) using a Google Form-based knowledge questionnaire before and after the education session. Results: The mean knowledge score increased from 76.2 to 87.1 (an 11-point gain); 76.5% of participants showed improved scores, and the proportion achieving the passing standard (≥80) rose from 41.2% to 88.2%. Conclusions: PGS-PL education effectively improved participants' knowledge related to local food-based balanced nutrition for children under two. Implication: These findings support the feasibility of PGS-PL as an education tool that can be integrated into Posyandu and Puskesmas nutrition promotion programs and scaled up in the subsequent effectiveness trial phase.